Efecto del estres hidrico sobre el rendimiento de tres variedades de tomate (Lyccopersicon esculentum, Mill.) - Mukandama, J.P.=700 1 Gonzalez, M.C.; Montilla, E.
(En, Es)
Ilus., 17 ref.
Keywords: LYCOPERSICON ESCULENTUM; ESTRES; RENDIMIENTO; VENEZUELA